2021
DOI: 10.3389/fcell.2021.755751
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Epigenetic Landscape of Murine Testis-Specific Histone Variants TH2A and TH2B Sharing the Same Bi-Directional Promoter

Abstract: Testis-specific histone variants are crucial to promote open chromatin structure to enable nucleosome disassembly in the final stages of spermiogenesis. However, even after histone replacement, mature sperm retain a proportion of these variants, the function of which is unknown. The present study aimed to understand the functional relevance of the retained H2B and H2A variants, TH2B and TH2A. While no literature is available on the phenotype of TH2A knockouts, TH2B/TH2A double knockout male mice are reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…It is a common practice to re-use publicly-available genomics data generated in the same cell types for integrative analysis. Taking advantage of public ChIP-seq data for histones and their modifications in mouse sperm cells ( Jung et al, 2019; Jung et al, 2017; Singh et al, 2021 ), we found that eccDNAs were significantly enriched with certain histone variants and modifications (Figure 2C), and 7.46% of sperm eccDNAs in total were intersected with at least one ChlP-seq peaks. Considering that histones occasionally retained in sperms might not generate strong ChIP-seq signals exceeding the peak calling cutoff, a meta-gene analysis of ChIP-seq signals at and around sperm eccDNA regions will likely provide more insights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common practice to re-use publicly-available genomics data generated in the same cell types for integrative analysis. Taking advantage of public ChIP-seq data for histones and their modifications in mouse sperm cells ( Jung et al, 2019; Jung et al, 2017; Singh et al, 2021 ), we found that eccDNAs were significantly enriched with certain histone variants and modifications (Figure 2C), and 7.46% of sperm eccDNAs in total were intersected with at least one ChlP-seq peaks. Considering that histones occasionally retained in sperms might not generate strong ChIP-seq signals exceeding the peak calling cutoff, a meta-gene analysis of ChIP-seq signals at and around sperm eccDNA regions will likely provide more insights.…”
Section: Resultsmentioning
confidence: 99%
“…Motif analysis and visualization were done by Two Sample Logo web server ( Vacic et al, 2006 ). Public ChIP-seq datasets ( Jung et al, 2019; Jung et al, 2017; Singh et al, 2021 ) were aligned to GRCm38 reference genome using Bowtie, and sorted and indexed using SAMtools version 1.7 ( Danecek et al, 2021 ). Picard MarkDuplicates version 2.18.14 was used to remove PCR duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…It is a common practice to reuse publicly available genomics data generated in the same cell types for integrative analysis. Taking advantage of public ChIP-seq data for histones and their modifications in mouse sperm cells ( Jung et al, 2019 ; Jung et al, 2017 ; Singh and Parte, 2021 ), we found that eccDNAs were significantly enriched with certain histone variants and modifications ( Figure 2C ), and 7.46% of sperm eccDNAs in total were intersected with at least one ChIP-seq peaks. Considering that histones occasionally retained in sperms might not generate strong ChIP-seq signals exceeding the peak calling cutoff, a meta-gene analysis of ChIP-seq signals at and around sperm eccDNA regions will likely provide more insights.…”
Section: Resultsmentioning
confidence: 99%
“…Histone variants and TPs also bear PTMs, which affects their binding affinity to DNA (Gupta et al, 2015(Gupta et al, , 2017Hazzouri et al, 2000;Kwak & Dohmae, 2016;Mishra et al, 2015;Pentakota et al, 2014;Pradeepa et al, 2009;Singh & Parte, 2021). Of note, TP2 acetylation reduces its ability to condense DNA (Pradeepa et al, 2009), suggesting that modified TPs may contribute to establish the final sperm epigenome.…”
Section: Posttranslational Modification Of Proteins Regulating the Nh...mentioning
confidence: 99%